Acceptability and perceived feasibility of adapted encounter decision aids on contraceptive methods: An interview study with healthcare providers and Chinese migrant women - Hankiz Dolan; Deborah Bateson; Mu Li; Rachel Thompson; Chun Wah Michael Tam; Carissa Bonner; Lyndal Trevena (Elsevier, 2022)
Objective: This study aimed to explore the perceived acceptability, usefulness, and feasibility of a suite of encounter decision aids (DAs) on contraceptive methods with Chinese migrant women living in Australia and healthcare providers. Methods: Semi-structured in-depth interviews with 22 Chinese migrant women and twenty healthcare providers were conducted. Transcribed data were analysed using the qualitative content analysis method. Results: Women perceived the DAs to be informative and useful. They suggested making the DAs available outside the clinical settings. Healthcare providers perceived the DAs to be comprehensive and valuable in informing women about contraceptive methods. Some providers had concerns as to the information load and the length of the DAs. Such concerns were eased when provided with an explanation of how to use the DAs. Most women and healthcare providers preferred the numerical format for side-effect probability information presentation. Conclusion: Making the encounter DAs available in both the Chinese and English languages can be valuable in assisting Chinese migrant women in making informed decisions about contraceptive methods. Innovation: This study is the first to evaluate the acceptability and perceived feasibility of patient decision aids with members of a migrant community in Australia. The findings highlight the need for disseminating the DAs both within and outside the clinical settings.